Narrow Bracketing and Dominated Choices - Rabin, Matthew; Weizsäcker, Georg (American Economic Review, 2009)
We show that any decision maker who “narrowly brackets” (evaluates decisions separately) and does not have constant-absolute-risk-averse preferences will make a first-order stochastically dominated combined choice in some simple pair of independent binary decisions. We also characterize the preference-contingent monetary cost from this mistake. Empirically, in a real-stakes laboratory experiment that replicates Tversky and Kahneman's (1981) experiment, 28 percent of participants choose dominated combinations. In a representative survey eliciting hypothetical large-stakes choices, higher proportions do so. Violation rates vary little with personal characteristics. Average preferences are prospect-theoretic, with an estimated 89 percent of people bracketing narrowly. (JEL D12, D81)